On the accuracy of approximation of a small celestial body motion using intermediate perturbed orbits calculated from two position vectors and three observations; Solar System Research; Vol. 49, iss. 1 - Shefer V. A. Vladimir Aleksandrovich (2015, 2015)
Title screen